Remedies for Glucose Intolerance – Are Traditional Herbal Concoctions for Diabetes Effective? (2015)
Background:Preventing or delaying the onset of diabetes in prediabetes has the potential to reduce the disease prevalence. Objective:The effectiveness of traditional herbal concoctions for diabetes in ameliorating glucose intolerance was investigated. Material and Methods:Oral glucose tolerance test (OGTT) was carried out by giving 500 mg/kg and 1000 mg/kg of individual plant extract and their aqueous herbal concoctions made from Musa sapientum + Allium sativum + Tetracarpidium conophorum; Gongronema latifolia + Bauhinia monandra; and Alstonia boonei + Mangifera indica to groups of rats, 30 and 60 minutes respectively prior to 3 g/kg of glucose load. Blood glucose levels were determined at 0, 10, 20, 30, 45, 60, 90, and 120 minutes post administration. Area under the curve (AUC) for OGTT and glycemic index were calculated and compared with the vehicle control and metformin (100 mg/kg). Level of significance was set at P<0.05. Results:Oral glucose tolerance test AUCs of individual plants were significantly lower than that of the vehicle control (P<0.05) but comparable with that of metformin (P>0.05) when given 30 minutes prior to glucose load. The OGTT curve AUCs of the three herbal concoctions were significantly higher than the two controls (P>0.05). Glycemic index of the concoctions were significantly higher than that of metformin (P>0.05) Conclusion:The herbal concoctions were not effective in ameliorating glucose intolerance. Individual plants were more effective when administered 30 minutes prior to glucose load. The individual herbs showed potentials to delay the onset of diabetes. Further investigations should be conducted on the numerous herbal concoctions used for diabetes.